2018
DOI: 10.1002/hep4.1208
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Approach Identifies a High Rate of Nonalcoholic Fatty Liver Disease With Advanced Fibrosis in Diabetes Clinics and At‐Risk Populations in Primary Care

Abstract: Noninvasive serum biomarkers (nonalcoholic fatty liver disease fibrosis score [NFS], fibrosis 4 score [FIB‐4], or enhanced liver fibrosis [ELF] test) are recommended as first‐line tools to determine the risk of advanced fibrosis in nonalcoholic fatty liver disease. We aimed to assess the utility of a pragmatic approach to screening for clinically significant fibrosis in primary care and diabetes clinics. We recruited 252 patients from an endocrine clinic or primary care facility. Anthropometric measurements, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 48 publications
2
74
0
1
Order By: Relevance
“…Among the 143 patients referred for NAFLD, steatosis or fatty liver, age‐specific FIB‐4 and NFS scores were provided or could be calculated using information in the referral for 54 (37.8%) patients. Twenty‐one patients had concordant “low” scores; the negative predictive value of NFS and FIB‐4 in combination for excluding definite/probable advanced fibrosis was 90.5%. Compared to those with concordant “low” scores at referral, patients with “indeterminate”/“high” FIB‐4 and/or NFS scores were 5.7 (95% CI: 1.1‐28.9; P = 0.036) times more likely to be diagnosed as having definite or probable advanced fibrosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 143 patients referred for NAFLD, steatosis or fatty liver, age‐specific FIB‐4 and NFS scores were provided or could be calculated using information in the referral for 54 (37.8%) patients. Twenty‐one patients had concordant “low” scores; the negative predictive value of NFS and FIB‐4 in combination for excluding definite/probable advanced fibrosis was 90.5%. Compared to those with concordant “low” scores at referral, patients with “indeterminate”/“high” FIB‐4 and/or NFS scores were 5.7 (95% CI: 1.1‐28.9; P = 0.036) times more likely to be diagnosed as having definite or probable advanced fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…In the hepatology clinic, patients underwent a clinical assessment that included anthropometric measurements, laboratory tests (routine biochemical, hematological, and serological assays), transient elastography, and liver imaging (computed tomography, magnetic resonance imaging, and/or ultrasound). Transient elastography was performed using FibroScan technology (Echosens, Paris, France) as previously described . At our center, LSM ≥8.2 kPa are used to identify clinically significant fibrosis (LSM ≥ 9.5 kPa for advanced fibrosis, and >13 kPa to indicate cirrhosis) .…”
Section: Methodsmentioning
confidence: 99%
“…It should be kept in mind that FIB‐4 and NFS do not adequately rule‐in advanced fibrosis (with a high rate of false‐positive results), thus further assessment with a more specific test is required in case of positive results. Several tests have been proposed for these cases, including ELF TM , Fibrometer® and TE . For instance, in a large, prospective study of a UK primary care referral pathway in 1,452 patients with NAFLD, Srivastava et al recently showed that a two‐step pathway (FIB‐4 followed by ELF TM performed in those with an indeterminate (score 1.3‐3.25) FIB‐4) reduced unnecessary referrals to liver specialists by 81%, and also markedly increased (five‐fold) the accurate referral of cases with advanced fibrosis.…”
Section: Referral Pathways From Primary Healthcare/diabetes Clinics Tmentioning
confidence: 99%
“…Several tests have been proposed for these cases, including ELF TM , 24,25 Fibrometer® 26 and TE. 23,[25][26][27] For instance, in a large, prospective study of a UK primary care referral pathway in 1,452 patients with NAFLD, Srivastava et al 24 recently showed that a two-step pathway (FIB-4 followed by ELF TM performed in those with an indeterminate (score 1.3-3.25) FIB-4) reduced unnecessary referrals to liver specialists by 81%, and also markedly increased (five-fold) the accurate referral of cases with advanced fibrosis. Importantly, because of the dual FIB-4 or NFS cut-offs, a significant proportion of patients (around 30%) fall in the intermediate risk category and cannot be correctly classified (indeterminate results).…”
Section: Primary Healthcarementioning
confidence: 99%
See 1 more Smart Citation